Application of waste water and waste residues of concrete mixing plant in concrete

By initially deposition, modification and dip in the concrete mixing station wastewater and waste slag, combined with modified polycarboxylic acid admixture, concrete with different strength grades was prepared, which solved the problem of wastewater and waste slag utilization, reduced production costs and increased Mechanical properties of concrete.

CN119430714APending Publication Date: 2025-02-14ZHEJIANG COMM CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411823530.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize wastewater and waste slag from concrete mixing stations, resulting in high production costs and unstable concrete mechanical properties.

Method used

By initially deposition, modification and di-deposition of waste water and waste residue, the recycling aggregate and modified aluminum hydroxychloride waste residue were obtained, and concrete of different strength grades was prepared in combination with modified polycarboxylic acid admixture.

Benefits of technology

It realizes efficient recycling and utilization of wastewater and waste slag in concrete mixing stations, reduces production costs, and significantly improves the mechanical properties and working properties of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an application of waste water and waste residues of a concrete mixing plant in concrete, which comprises the following steps: firstly mixing the waste water and the waste residues of the concrete mixing plant, removing large-particle suspended solids and silt after primary sedimentation, then separating to obtain recycled aggregate and waste slurry water, then adding aluminum chlorohydrate into the waste slurry water for mixing, and finally adding the recycled aggregate into the waste slurry water for mixing. After secondary precipitation, separating to obtain recycled water and aluminum chlorohydrate modified waste residues; the preparation method comprises the following steps: firstly, adding stearyl vinyl ether / MA copolymer and allyl-alpha-D-glucopyranoside into recycled water, stirring and preheating, then adding sodium persulfate, calcined kaolin and strontium thioglycolate, continuously carrying out heat preservation and stirring, then adding acrylic acid and sodium methallyl sulfonate for reaction, and after the reaction is finished, carrying out post-treatment to obtain a modified polycarboxylic acid additive; and mixing the cementing material, the aggregate, the aluminum chlorohydrate modified waste residue, the modified polycarboxylic acid additive and fresh water to obtain the C40-C80 concrete. The waste water and the waste residues of the concrete mixing plant are recycled for production of concrete with different strength grades, the production cost is reduced, and the mechanical property of the concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to application of waste water and waste residue from a concrete mixing station in concrete. Background Art

[0002] As the construction industry increases its efforts to protect the environment, many concrete production companies are also paying more and more attention to the investment in wastewater treatment. Studies have shown that wastewater will have a certain impact on the performance of cement, but it is within the range of cement standards and has little effect on the flexural strength and compressive strength of cement; studies have also shown that the standard consistency water consumption of cement is positively correlated with the amount of wastewater added. For every 20% increase in wastewater, its water consumption will increase by about 0.5%. When wastewater completely replaces clean water, its total water consumption will increase by about 2.3%; at the same time, water consumption is positively correlated with the solid content of wastewater, that is, the higher the solid content, the greater the cement water consumption. Not only that, as the amount and concentration of wastewater increase, the setting time of cement will be extended.

[0003] Currently, Borger et al. studied the effect of wastewater on the compressive strength, sulfate resistance, workability and setting time of concrete. Sandrolini studied the preparation of fresh concrete by slurry reuse. The results showed that within 28 days, the compressive strength of concrete was at least 96% of the compressive strength of the control concrete. Low studied the effect of wastewater on the working energy and hardening properties of concrete. The results showed that wastewater concrete met the requirements of European standard BSEN1008 in terms of compressive strength, setting time, drying shrinkage, etc. Chatveera studied the production of concrete using wastewater and studied the slump, compressive strength and elastic modulus of concrete. Their results showed that the wastewater had a high alkali content, which may increase the porosity of concrete and reduce the strength of the matrix; as the proportion of wastewater increased, the weight loss and drying shrinkage caused by acid attack also increased. Researchers from Greece studied the chemical properties of wastewater, including chlorine, sulfate and pH. The results showed that the pH value of wastewater was high, exceeding 11.5, and the chemical properties met the ASTM standard; the compressive strength of all concrete mixed with wastewater was higher than that of the control concrete specimens.

[0004] Studies have shown that the workability of concrete will also change with the amount of wastewater added. The addition of wastewater can increase the fluidity of mortar and concrete and reduce the loss of fluidity, but there will also be a situation where fluidity is reduced; some studies have also shown that when the concentration of wastewater added is less than 5%, the fluidity of concrete does not change much, it will drop rapidly when it exceeds 5%, and it will decrease significantly when it exceeds 10%, and the slump loss over time is also very large. The conclusion drawn by Leng Fasheng et al. from the experimental data of the study on the mixing performance of C30 and C40 concrete is contrary to this. They concluded through experiments that the initial slump value of concrete mixed with wastewater is not much different from that of concrete mixed with tap water; this may be because the effect of wastewater on concrete is related to the design grade of concrete. The lower the grade, the greater the slump loss and expansion loss, and the higher the grade, the smaller the loss. Some people believe that after the addition of wastewater, the early strength of concrete will not fluctuate too much, but it will increase the 28-day strength; however, some studies have shown that it will increase the early strength and have little effect on the later strength; some studies have shown that its addition will increase both the early and later strengths, and the concrete design grade will also affect the strength change. The mechanical properties of concrete will also be affected by the amount and concentration of wastewater. When the amount of wastewater exceeds a certain limit, the strength of concrete will be negatively correlated with the wastewater, that is, the higher the amount of wastewater, the lower the strength of concrete. Under the condition of a certain amount of wastewater, the strength of concrete is negatively correlated with the concentration of wastewater, that is, the higher the concentration of wastewater, the lower the strength of concrete. Studies have also shown that the effects of different amounts of wastewater and different concentrations of wastewater on concrete are related to the design grade of concrete. Zhao Tongwei believes that appropriate amounts of wastewater have no adverse effects on the performance of medium and low strength grade concrete. Long Weiming combined strength and slump and believed that the amount of wastewater is most suitable when it is 50%. Studies by Mu Jianming and others have shown that the concentration of wastewater will affect the working performance of concrete, and the higher the concentration of wastewater, the more obvious the deterioration of the mechanical properties of concrete. Wastewater also has a significant effect on the later shrinkage of concrete.

[0005] As the storage time of mixing station waste increases, the cementitious materials in it continue to undergo hydration reactions and lose their bonding properties; the wastewater from mixing stations contains some mud and sand that affect the quality of concrete, and the mud and sand content is unstable, resulting in large fluctuations in the quality of concrete when the wastewater is recycled, making it difficult to control the quality of the poured concrete. Based on the waste slurry recycling technology, it is urgent to establish a prediction model for the compressive strength of concrete of different strength grades, obtain the optimal mixing ratio of mixing waste slag and wastewater, and ensure the stability of the strength of mixing waste slag and wastewater concrete specimens. Summary of the invention

[0006] The problem to be solved by the present invention is to provide an application of wastewater and waste residue from a concrete mixing station in concrete in view of the above-mentioned deficiencies in the prior art, which achieves the purpose of recycling the wastewater and waste residue from the concrete mixing station for the production of concrete of different strength grades, reducing production costs and improving the mechanical properties of concrete.

[0007] The above-mentioned object of the present invention is achieved through the following technical solutions: A method for using wastewater and waste residue from a concrete mixing station in concrete comprises the following steps: S1 first mixes the wastewater and waste residue of the concrete mixing plant, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to the waste slurry water for mixing, and separates to obtain recycled water and aluminum chlorohydrate-modified waste residue after secondary sedimentation; S2: first adding stearyl vinyl ether / MA copolymer and allyl-α-D-pyranoglucoside to the recycled water obtained in S1, stirring and preheating, then adding sodium persulfate, calcined kaolin and strontium thioglycolate, continuing to keep warm and stir, then adding acrylic acid and sodium methacrylic acid to react, and after the reaction is completed, post-treating to obtain a modified polycarboxylic acid admixture; S3 mixes 400.00~580.00kg / m³ of cementitious material, 1781.00~1831.00kg / m³ of aggregate containing recycled aggregate obtained in S1, 10~20% of the total weight of the aggregate modified aluminum chlorohydrate obtained in S1, 1.20~1.80% of the total weight of the cementitious material, and 22.41%~39.00% of the total weight of the cementitious material, to obtain C40~C80 concrete.

[0008] Furthermore, in S1, the concentration of the aluminum chlorohydrate in the waste slurry water is controlled to be 15-18 kg / m³.

[0009] Furthermore, in the S1, aluminum chlorohydrate is added to fresh water, stirred until the aluminum chlorohydrate is dissolved, and then the aluminum chlorohydrate aqueous solution is pumped into the waste slurry water, mixed and modified at 40-50° C. for 30-60 minutes, during which the mixture is stirred 4-6 times at equal time intervals, each time at 100-200 rpm for 3-5 minutes.

[0010] Furthermore, in S2, the molar ratio of the stearyl vinyl ether / MA copolymer, allyl-α-D-pyranoglucoside, sodium persulfate, calcined kaolin, strontium thioglycolate, acrylic acid and sodium methacrylate sulfonate is controlled to be 45.00~60.00:15.00~20.00:1.00~2.00:1.00~2.00:3.00~6.00:100.00:10.00~15.00.

[0011] Furthermore, in S2, the concentration of acrylic acid in the recovered water is controlled to be 100-300 kg / m³.

[0012] Furthermore, in S2, the stirring speed is controlled to be 500-800 rpm, the preheating temperature is 60-80° C., the reaction temperature is 80-100° C., and the reaction time is 1-3 h.

[0013] Furthermore, in S2, after the reaction is completed, the pH of the reaction solution is adjusted to 6.5-7.0 with a 30 wt % sodium hydroxide solution, and the solid content of the modified polycarboxylic acid admixture is adjusted to 20-40%.

[0014] Furthermore, in S3, aggregate and the aluminum chlorohydrate modified waste residue obtained in S1 are first added to the mixer, mixed for 1 minute, and then half of the fresh water is added and stirred for 2 minutes. Then, the cementitious material, the modified polycarboxylic acid admixture and the remaining fresh water are added by the same mixing method, and wet mixed for 3 minutes until the mixture is evenly dispersed. Then, the mixture is added to the test mold in layers and batches, vibrated and compacted, and demolded after 20 hours of molding, and cured to obtain C40~C80 concrete.

[0015] Further, in S3, the cementitious material includes 160.00-442.00 kg / m³ cement, 80.00-94.00 kg / m³ mineral powder, and 54.00-160.00 kg / m³ fly ash.

[0016] Furthermore, in S3, the fly ash accounts for 9.31-40.00% (fly ash replacement rate) of the total weight of the cementitious material.

[0017] Further, in S3, the aggregate includes 84.00-158.00 kg / m³ of river sand with a particle size of less than 5 mm, 598.00-755.00 kg / m³ of machine-made sand, 788.00-826.00 kg / m³ of large crushed stone with a particle size of 10-20 mm, and 197.00-207.00 kg / m³ of small crushed stone with a particle size of less than 10 mm, and the river sand, machine-made sand, large crushed stone and small crushed stone are independently selected from unrecovered aggregate and / or the recycled aggregate obtained in S1. That is, after the recycled aggregate and waste slurry are separated in S1, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecovered aggregate according to the screening level, mixed evenly, and directly used for the subsequent aggregate raw materials.

[0018] Furthermore, in S3, the mass ratio of the unrecovered aggregate to the recycled aggregate in the river sand, machine-made sand, large crushed stone and small crushed stone is independently 3-7:7-3.

[0019] Furthermore, in S3, the river sand and machine-made sand account for 42.00-46.00% (sand ratio) of the total weight of the aggregate.

[0020] Furthermore, in S3, the machine-made sand accounts for 79.95-89.99% (machine-made sand replacement rate) of the total weight of the river sand and the machine-made sand.

[0021] Furthermore, in S3, the mass ratio of the large gravel to the small gravel is 3.99-4.01.

[0022] Furthermore, in S3, the large gravel and the small gravel are limestone.

[0023] In summary, the beneficial technical effects of the present invention are: 1. In order to reduce the emission of solid waste caused by concrete production and reduce the waste of land resources and environmental damage caused by the stacking of solid waste, the present invention studies the preparation technology of concrete with different strength grades (C40-C80) of mixing waste slag, obtains recycled aggregate (mixing waste sand and gravel) through sand and gravel separation technology, and realizes the repeated recycling of waste sand and gravel; adopts waste slurry recycling technology to separate and modify mixing waste water into recycled water and aluminum chlorohydrate modified waste slag, and studies the fluidity of mortar with different recycled aggregate dosages and the mechanical properties of mortar at different ages. At the same time, research on the preparation technology of concrete of different strength grades based on mixing waste residue is carried out, and its active technology is developed. Aluminum chlorohydrate modified waste residue is prepared by utilizing the synergistic effect of wastewater and waste residue from different concrete mixing plants, and its influence and action law on the performance of cement-based materials are studied. Modified polycarboxylic acid admixtures compatible with aluminum chlorohydrate modified waste residue are developed to form key technologies for the preparation and application of concrete of different strength grades based on mixing waste residue, and wastewater and waste residue from concrete mixing plants are recycled and utilized in the production of concrete of different strength grades, thereby reducing production costs and improving the mechanical properties of concrete. 2. The aluminum chlorohydrate modified waste residue obtained by primary precipitation, modification and secondary precipitation in the present invention can synergize with the recycled aggregate which is also solid waste to promote the reaction between silicon, aluminum and calcium solid phases, which can not only significantly improve the mechanical properties of concrete, but also effectively improve the workability of concrete; the present invention further studies the optimal ratio of aluminum chlorohydrate modified waste residue and recycled aggregate to achieve the best concrete performance, and through a series of experiments, determines the appropriate dosage of aluminum chlorohydrate modified waste residue and recycled aggregate in concrete of different strength grades, thereby ensuring that the concrete has good construction performance while meeting the strength requirements; 3. In the modified polycarboxylic acid admixture of the present invention, under the action of sodium persulfate, calcined kaolin and strontium thioglycolate, acrylic acid, allyl-α-D-pyranoglucoside, sodium methyl propylene sulfonate, and stearyl vinyl ether / MA copolymer are polymerized and connected in sequence in the presence of recycled water. The admixture obtained can not only inhibit the negative impact of minerals in recycled water, but also synergize with aluminum chlorohydrate modified waste residue to enhance the bonding force between aluminum chlorohydrate modified waste residue and gelling system, and further improve the comprehensive performance of concrete. By adjusting the molecular structure and dosage of the admixture, the setting time, fluidity and durability of the concrete can be effectively controlled, making it more adaptable to different engineering requirements. DETAILED DESCRIPTION

[0024] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0025] Embodiment 1: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 16kg / m³, mixes and modifies at 45°C for 45 minutes, stirs 5 times at equal time intervals, and stirs at 165rpm for 3 minutes each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: firstly add 17.20 molar parts of stearyl vinyl ether / MA copolymer and 18.60 molar parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, preheat to 70°C with stirring at 750 rpm, then add 1.24 molar parts of sodium persulfate, 1.24 molar parts of calcined kaolin and 4.08 molar parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 molar parts of acrylic acid and 12.80 molar parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 200 kg / m³, react at 90°C for 1.5 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, 400.00kg / m³ cementitious material, 1824.00kg / m³ aggregate containing recycled aggregate obtained in S1, 328.32kg / m³ aluminum chlorohydrate modified waste residue, 6.00kg / m³ modified polycarboxylic acid admixture, and 156.00kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture into the test mold in layers and batches, vibrate and compact, demould after forming for 20 hours, and maintain to obtain C40 concrete; Among them, the cementitious materials include 160.00kg / m³ cement, 80.00kg / m³ mineral powder, and 160.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 84.00kg / m³ river sand with a particle size below 5mm, 755.00kg / m³ machine-made sand, 788.00kg / m³ large crushed stone with a particle size of 10-20mm, and 197.00kg / m³ small crushed stone with a particle size below 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0026] After testing, the 7d compressive strength of C40 concrete is 25.2MPa, and the 28d compressive strength is 46.3MPa.

[0027] The present invention is further described in conjunction with specific implementation modes.

[0028] Embodiment 2: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 16kg / m³, mixes and modifies at 45°C for 45 minutes, stirs 5 times at equal time intervals, and stirs at 165rpm for 3 minutes each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: firstly add 17.20 molar parts of stearyl vinyl ether / MA copolymer and 18.60 molar parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, preheat to 70°C with stirring at 750 rpm, then add 1.24 molar parts of sodium persulfate, 1.24 molar parts of calcined kaolin and 4.08 molar parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 molar parts of acrylic acid and 12.80 molar parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 200 kg / m³, react at 90°C for 1.5 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, including 440.00 kg / m³ cementitious material, 1798.00 kg / m³ aggregate containing recycled aggregate obtained in S1, 179.80 kg / m³ aluminum chlorohydrate modified waste residue, 5.28 kg / m³ modified polycarboxylic acid admixture, and 152.00 kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture to the test mold in layers and batches, vibrate and compact, demold after 20 hours of molding, and cure to obtain C50 concrete; Among them, the cementitious materials include 266.00kg / m³ cement, 87.00kg / m³ mineral powder, and 87.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 158.00kg / m³ river sand with a particle size of less than 5mm, 633.00kg / m³ machine-made sand, 806.00kg / m³ large crushed stone with a particle size of 10-20mm, and 201.00kg / m³ small crushed stone with a particle size of less than 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0029] After testing, the 7d compressive strength of C50 concrete is 35.8MPa, and the 28d compressive strength is 54.2MPa.

[0030] The present invention is further described in conjunction with specific implementation modes.

[0031] Embodiment 3: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 16kg / m³, mixes and modifies at 45°C for 45 minutes, stirs 5 times at equal time intervals, and stirs at 165rpm for 3 minutes each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: firstly add 17.20 molar parts of stearyl vinyl ether / MA copolymer and 18.60 molar parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, preheat to 70°C with stirring at 750 rpm, then add 1.24 molar parts of sodium persulfate, 1.24 molar parts of calcined kaolin and 4.08 molar parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 molar parts of acrylic acid and 12.80 molar parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 200 kg / m³, react at 90°C for 1.5 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, including 479.00 kg / m³ cementitious material, 1781.00 kg / m³ aggregate containing recycled aggregate obtained in S1, 267.15 kg / m³ aluminum chlorohydrate modified waste residue, 6.70 kg / m³ modified polycarboxylic acid admixture, and 150.00 kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture into the test mold in layers and batches, vibrate and compact, demould after 20 hours of molding, and cure to obtain C60 concrete; Among them, cementitious materials include 244.00kg / m³ cement, 94.00kg / m³ mineral powder, and 141.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 150.00kg / m³ river sand with a particle size of less than 5mm, 598.00kg / m³ machine-made sand, 826.00kg / m³ large crushed stone with a particle size of 10-20mm, and 207.00kg / m³ small crushed stone with a particle size of less than 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0032] After testing, the 7d compressive strength of C60 concrete is 48.9MPa, and the 28d compressive strength is 69.6MPa.

[0033] The present invention is further described in conjunction with specific implementation modes.

[0034] Embodiment 4: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 16kg / m³, mixes and modifies at 45°C for 45 minutes, stirs 5 times at equal time intervals, and stirs at 165rpm for 3 minutes each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: firstly add 17.20 molar parts of stearyl vinyl ether / MA copolymer and 18.60 molar parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, preheat to 70°C with stirring at 750 rpm, then add 1.24 molar parts of sodium persulfate, 1.24 molar parts of calcined kaolin and 4.08 molar parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 molar parts of acrylic acid and 12.80 molar parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 200 kg / m³, react at 90°C for 1.5 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, 580.00kg / m³ cementitious material, 1831.00kg / m³ aggregate containing recycled aggregate obtained in S1, 366.20kg / m³ aluminum chlorohydrate modified waste residue, 10.44kg / m³ modified polycarboxylic acid admixture, and 130.00kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture to the test mold in layers and batches, vibrate and compact, demold after 20 hours of molding, and cure to obtain C80 concrete; Among them, cementitious materials include 442.00kg / m³ cement, 84.00kg / m³ mineral powder, and 54.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 128.00kg / m³ river sand with a particle size of less than 5mm, 698.00kg / m³ machine-made sand, 804.00kg / m³ large crushed stone with a particle size of 10-20mm, and 201.00kg / m³ small crushed stone with a particle size of less than 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0035] After testing, the 7d compressive strength of C80 concrete is 70.5MPa, and the 28d compressive strength is 92.3MPa.

[0036] The present invention is further described in conjunction with specific implementation modes.

[0037] Embodiment 5: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue of the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 15kg / m³, mixes and modifies at 40°C for 30min, stirs 5 times at equal time intervals, and stirs at 100rpm for 4min each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: firstly add 17.20 molar parts of stearyl vinyl ether / MA copolymer and 18.60 molar parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, preheat to 70°C with stirring at 750 rpm, then add 1.24 molar parts of sodium persulfate, 1.24 molar parts of calcined kaolin and 4.08 molar parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 molar parts of acrylic acid and 12.80 molar parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 200 kg / m³, react at 90°C for 1.5 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, 400.00kg / m³ cementitious material, 1824.00kg / m³ aggregate containing recycled aggregate obtained in S1, 328.32kg / m³ aluminum chlorohydrate modified waste residue, 6.00kg / m³ modified polycarboxylic acid admixture, and 156.00kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture into the test mold in layers and batches, vibrate and compact, demould after forming for 20 hours, and maintain to obtain C40 concrete; Among them, the cementitious materials include 160.00kg / m³ cement, 80.00kg / m³ mineral powder, and 160.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 84.00kg / m³ river sand with a particle size below 5mm, 755.00kg / m³ machine-made sand, 788.00kg / m³ large crushed stone with a particle size of 10-20mm, and 197.00kg / m³ small crushed stone with a particle size below 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0038] After testing, the 7d compressive strength of C40 concrete is 26.4MPa, and the 28d compressive strength is 45.8MPa.

[0039] The present invention is further described in conjunction with specific implementation modes.

[0040] Embodiment 6: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 18kg / m³, mixes and modifies at 45°C for 60min, stirs 5 times at equal time intervals, and stirs at 200rpm for 5min each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: firstly add 17.20 molar parts of stearyl vinyl ether / MA copolymer and 18.60 molar parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, preheat to 70°C with stirring at 750 rpm, then add 1.24 molar parts of sodium persulfate, 1.24 molar parts of calcined kaolin and 4.08 molar parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 molar parts of acrylic acid and 12.80 molar parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 200 kg / m³, react at 90°C for 1.5 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, 400.00kg / m³ cementitious material, 1824.00kg / m³ aggregate containing recycled aggregate obtained in S1, 328.32kg / m³ aluminum chlorohydrate modified waste residue, 6.00kg / m³ modified polycarboxylic acid admixture, and 156.00kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture into the test mold in layers and batches, vibrate and compact, demould after forming for 20 hours, and maintain to obtain C40 concrete; Among them, the cementitious materials include 160.00kg / m³ cement, 80.00kg / m³ mineral powder, and 160.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 84.00kg / m³ river sand with a particle size below 5mm, 755.00kg / m³ machine-made sand, 788.00kg / m³ large crushed stone with a particle size of 10-20mm, and 197.00kg / m³ small crushed stone with a particle size below 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0041] After testing, the 7d compressive strength of C40 concrete is 24.7MPa, and the 28d compressive strength is 47.2MPa.

[0042] The present invention is further described in conjunction with specific implementation modes.

[0043] Embodiment 7: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 16kg / m³, mixes and modifies at 45°C for 45 minutes, stirs 5 times at equal time intervals, and stirs at 165rpm for 3 minutes each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: first add 45.00 mole parts of stearyl vinyl ether / MA copolymer and 15.00 mole parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, stir and preheat to 60°C at 500 rpm, then add 1.00 mole parts of sodium persulfate, 1.00 mole parts of calcined kaolin and 3.00 mole parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 mole parts of acrylic acid and 10.00 mole parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 100 kg / m³, react at 80°C for 1.0 h, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, 400.00kg / m³ cementitious material, 1824.00kg / m³ aggregate containing recycled aggregate obtained in S1, 328.32kg / m³ aluminum chlorohydrate modified waste residue, 6.00kg / m³ modified polycarboxylic acid admixture, and 156.00kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture into the test mold in layers and batches, vibrate and compact, demould after forming for 20 hours, and maintain to obtain C40 concrete; Among them, the cementitious materials include 160.00kg / m³ cement, 80.00kg / m³ mineral powder, and 160.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 84.00kg / m³ river sand with a particle size below 5mm, 755.00kg / m³ machine-made sand, 788.00kg / m³ large crushed stone with a particle size of 10-20mm, and 197.00kg / m³ small crushed stone with a particle size below 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0044] After testing, the 7d compressive strength of C40 concrete is 30.5MPa, and the 28d compressive strength is 45.6MPa.

[0045] The present invention is further described in conjunction with specific implementation modes.

[0046] Embodiment 8: The present invention discloses an application of wastewater and waste residue from a concrete mixing station in concrete, comprising the following steps: S1 first mixes the wastewater and waste residue from the concrete mixing station, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to fresh water, stirs until the aluminum chlorohydrate is dissolved, pumps the aluminum chlorohydrate aqueous solution into the waste slurry water, controls the concentration of aluminum chlorohydrate in the waste slurry water to be 16kg / m³, mixes and modifies at 45°C for 45 minutes, stirs 5 times at equal time intervals, and stirs at 165rpm for 3 minutes each time, and separates to obtain recycled water and aluminum chlorohydrate modified waste residue after secondary sedimentation; S2: first add 60.00 mol parts of stearyl vinyl ether / MA copolymer and 20.00 mol parts of allyl-α-D-pyranoglucoside to the recycled water obtained in S1, stir and preheat to 80°C at 800 rpm, then add 2.00 mol parts of sodium persulfate, 2.00 mol parts of calcined kaolin and 6.00 mol parts of strontium thioglycolate, continue to keep warm and stir, then add 100.00 mol parts of acrylic acid and 15.00 mol parts of sodium methacrylate sulfonate, control the concentration of acrylic acid in the recycled water to 300 kg / m³, react at 100°C for 3.0 hours, and after the reaction is completed, adjust the pH of the reaction solution to 6.8 with 30wt% sodium hydroxide solution and adjust the solid content to 25% to obtain a modified polycarboxylic acid admixture; S3 prepares raw materials, 400.00kg / m³ cementitious material, 1824.00kg / m³ aggregate containing recycled aggregate obtained in S1, 328.32kg / m³ aluminum chlorohydrate modified waste residue, 6.00kg / m³ modified polycarboxylic acid admixture, and 156.00kg / m³ fresh water; when mixing, first add the aggregate and aluminum chlorohydrate modified waste residue obtained in S1 into the mixer, mix for 1 minute, then add half of the fresh water, stir for 2 minutes, then add the cementitious material, modified polycarboxylic acid admixture and the remaining fresh water by the same mixing method, wet mix for 3 minutes until the mixture is evenly dispersed, then add the mixture into the test mold in layers and batches, vibrate and compact, demould after forming for 20 hours, and maintain to obtain C40 concrete; Among them, the cementitious materials include 160.00kg / m³ cement, 80.00kg / m³ mineral powder, and 160.00kg / m³ fly ash; After S1 separates the recycled aggregate and waste slurry, the river sand, machine-made sand, large crushed stone and small crushed stone in the recycled aggregate are put into the silo of unrecycled aggregate according to the screening level and mixed evenly, and directly used as the subsequent aggregate raw materials; Aggregates include 84.00kg / m³ river sand with a particle size below 5mm, 755.00kg / m³ machine-made sand, 788.00kg / m³ large crushed stone with a particle size of 10-20mm, and 197.00kg / m³ small crushed stone with a particle size below 10mm. The mass ratio of unrecycled aggregate to recycled aggregate in the aggregate is approximately 7:3. The crushed stone of large crushed stone and small crushed stone is limestone.

[0047] After testing, the 7d compressive strength of C40 concrete is 34.2MPa, and the 28d compressive strength is 44.3MPa.

[0048] Comparative Example 1 is an application of wastewater and waste residue from a concrete mixing station disclosed in the present invention in concrete. The difference from Example 4 is that aluminum chlorohydrate is not used to modify the waste residue.

[0049] After testing, the 7d compressive strength of C80 concrete is 66.4MPa, and the 28d compressive strength is 75.5MPa.

[0050] Comparative Example 2 is an application of wastewater and waste residue from a concrete mixing station disclosed in the present invention in concrete. The difference from Example 4 is that a commercially available polycarboxylic acid high-performance water-reducing agent is used instead of the modified polycarboxylic acid admixture.

[0051] After testing, the 7d compressive strength of C80 concrete is 54.8MPa, and the 28d compressive strength is 69.2MPa.

[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. Application of wastewater and waste residue from a concrete mixing station in concrete, characterized by: The following steps are included: S1 first mixes the wastewater and waste residue of the concrete mixing plant, removes large suspended solids and silt after primary sedimentation, and then separates to obtain recycled aggregate and waste slurry water, then adds aluminum chlorohydrate to the waste slurry water for mixing, and separates to obtain recycled water and aluminum chlorohydrate-modified waste residue after secondary sedimentation; S2: first adding stearyl vinyl ether / MA copolymer and allyl-α-D-pyranoglucoside to the recycled water obtained in S1, stirring and preheating, then adding sodium persulfate, calcined kaolin and strontium thioglycolate, continuing to keep warm and stir, then adding acrylic acid and sodium methacrylic acid to react, and after the reaction is completed, post-treating to obtain a modified polycarboxylic acid admixture; S3 mixes 400.00~580.00kg / m³ of cementitious material, 1781.00~1831.00kg / m³ of aggregate containing recycled aggregate obtained in S1, 10~20% of the total weight of the aggregate modified aluminum chlorohydrate obtained in S1, 1.20~1.80% of the total weight of the cementitious material, and 22.41%~39.00% of the total weight of the cementitious material, to obtain C40~C80 concrete.

2. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 1, characterized in that: In S1, the concentration of the aluminum chlorohydrate in the waste slurry water is controlled to be 15-18 kg / m³.

3. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 2 is characterized by: In the S1, aluminum chlorohydrate is added to fresh water, stirred until the aluminum chlorohydrate is dissolved, and then the aluminum chlorohydrate aqueous solution is pumped into the waste slurry water, mixed and modified at 40-50° C. for 30-60 minutes, during which stirring is performed 4-6 times at equal time intervals, each time stirring at 100-200 rpm for 3-5 minutes.

4. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 1 is characterized by: In S2, the concentration of acrylic acid in the recovered water is controlled to be 100-300 kg / m³.

5. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 4, characterized in that: In S2, the stirring speed is controlled to be 500-800 rpm, the preheating temperature is 60-80° C., the reaction temperature is 80-100° C., and the reaction time is 1-3 h.

6. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 5, characterized in that: In S2, after the reaction is completed, the pH of the reaction solution is adjusted to 6.5-7.0 with a 30 wt % sodium hydroxide solution, and the solid content of the modified polycarboxylic acid admixture is adjusted to 20-40%.

7. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 1, characterized in that: In S3, aggregate and the aluminum chlorohydrate modified waste residue obtained in S1 are first added to the mixer, mixed for 1 minute, and then half of the fresh water is added and stirred for 2 minutes. Then, the cementitious material, the modified polycarboxylic acid admixture and the remaining fresh water are added by the same mixing method, and wet mixed for 3 minutes until the mixture is evenly dispersed. Then, the mixture is added to the test mold in layers and batches, vibrated and compacted, and demolded after 20 hours of molding, and cured to obtain C40~C80 concrete.

8. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 7, characterized in that: In S3, the cementitious material includes 160.00-442.00 kg / m³ cement, 80.00-94.00 kg / m³ mineral powder, and 54.00-160.00 kg / m³ fly ash.

9. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 7, characterized in that: In S3, the aggregate includes 84.00~158.00kg / m³ of river sand with a particle size of less than 5mm, 598.00.00.00kg / m³ of machine-made sand, 788.00.00.00kg / m³ of large crushed stone with a particle size of 10-20mm, and 197.00.00kg / m³ of small crushed stone with a particle size of less than 10mm, and the river sand, machine-made sand, large crushed stone and small crushed stone are each independently selected from unrecycled aggregate and / or recycled aggregate obtained in S1.

10. The use of wastewater and waste residue from a concrete mixing station in concrete according to claim 9, characterized in that: In S3, the mass ratio of the unrecovered aggregate to the recycled aggregate in the river sand, machine-made sand, large crushed stone and small crushed stone is independently 3-7:7-3.